ANALISIS PENGGUNAAN HUTANG TERHADAP RETURN ON EQUITY PADA PT. ALAM SUTRA REALTY, TBK - Alvitra, Aldi; Pratiwi, Aliah (Jurnal Manajemen, 2023)
This study aims to know and analyze the use of debt on Return On Equity at PT. Alam Sutra Realty, Tbk. This research is an associative type using a research instrument in the form of a list of tables containing data on total short-term debt, total long-term debt, net income and total equity at PT. Alam Sutra Realty, Tbk. The population used in this study is the financial statements of PT. Alam Sutra Realty, Tbk in the form of a balance sheet and profit and loss report since being listed on the IDX from 2007 to 2021, namely for 14 years. The sample in this study is the financial statements of PT. Alam Sutra Realty, Tbk in the form of a balance sheet and income statement for 10 years, from 2012 to 2021. The sampling technique used in this study was purposive sampling. Data collection techniques using documentation and literature study. Data analysis techniques using the classical assumption test, multiple linear regression, correlation coefficient, determination test, t test and f test. The results showed that both partially and simultaneously short-term debt and long-term debt have no effect on Return On Equity at PT. Alam Sutra Realty, Tbk.